Pengaruh Karakter Jalan Terhadap Kecelakaan Lalu Lintas Pada Ruas Jalan Pangkep-Barru Di Kabupaten Pangkajene Dan Kepulauan - Saparuddin, Saparuddin (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The aim of the research is to determine the effect of road character on traffic accidents on the Pangkep-Barru road section in Pangkajene and Pulau Regency. . Along with the development of time, humans always need something that can provide comfort and convenience that can be done efficiently and effectively to live their lives. This is the availability of adequate infrastructure facilities and infrastructure, where infrastructure has a very important role in the smooth driving of national development, for example in the field of transportation. The condition of the Poros Pangkep-Barru highway in the Pangkajene Regency and the Islands with a length of 33.3 KM has several shortcomings, such as many potholes, slippery roads, and bumpy roads. This can happen because the Pangkajene and Islands areas have high rainfall intensity and the large number of vehicles that cross the road. In addition to the road conditions mentioned above, there are other shortcomings, namely street lighting facilities or PJU lights on the Poros Pangkep-Barru highway in the Pangkajene and Islands Regency areas which have insufficient lighting so that it can affect the level of vigilance of motorists. Based on data on cases of accidents that occurred on the Poros Pangkep-Barru highway in the Pangkajene and Islands Regency areas, one of the factors that caused the accident was the road factor